Pengaruh Experiential Marketing Terhadap Revisit Intention Melalui Customer Satisfaction Sebagai Variabel Intervening Di Glamping Lakeside Rancabali - Paulina, Paulina; Facrureza, Dewanta (Jurnal Syntax Fusion, 2023)
Experience-based tourism has replaced good-based tourism in this modern era. The accommodation industry, such as glamping, must adapt to market developments. Experiential Marketing, which creates unforgettable experiences for tourists, is needed to promote glamping. Tourists may want to visit again if they get a memorable experience. This study examines the impact of Experiential Marketing Glamping Lakeside Rancabali on Customer Satisfaction and Revisit Intention. This study used a quantitative research method with a sample of 100 respondents who were selected using a purposive non-probability technique. The selected sample is tourists who have stayed at Glamping Lakeside Rancabali. The T test shows that Customer Satisfaction is partially affected by the Sense, Think, and Relate. Revisit Intention is partially influenced by Act, Relate, and Customer Satisfaction. The F test shows that all Experiential Marketing variables together significantly affect Customer Satisfaction and Revisit Intention. According to the route analysis test, Customer Satisfaction can mediate the Sense, Feel, and Think variables. According to the Determination Coefficient Test, experiential marketing has a 55.4% impact on customer satisfaction and a 69.8% impact on revisit intention.